First Detection of Honey Bee Viruses in Wax Moth - Prapun Traiyasut (Science Faculty of Chiang Mai University, 2019)
Larvae of greater wax moth (Galleria mellonella) attacking the colonies of Apis cerana japonica were collected from Chiba Prefecture, Japan on December 25, 2012. By RT-PCR method, samples were tested positive for Israeli Acute Paralysis Virus (IAPV) and Black Queen Cell Virus (BQCV). These viruses were observed in both worker bees and the wax moth larvae infesting the colonies, although with a lower frequency in the worker bees. The IAPV isolates showed 97% sequence similarity to isolates from China and the BQCV isolates showed 99% sequence similarity to isolates from Korea. This is the first report of the detection of honey bee viruses in wax moth larvae infesting A. cerana japonica.